Profile of bevacizumab in the treatment of platinum-resistant ovarian cancer: current perspectives - McClung EC; Wenham RM (Dove Medical Press, 2016)
E Clair McClung, Robert M WenhamDepartment of Gynecologic Oncology, H. Lee Moffitt Cancer Center, Tampa, FL, USAAbstract: Patients with platinum-resistant ovarian cancer have progression of disease within 6 months of completing platinum-based chemotherapy. While several chemotherapeutic options exist for the treatment of platinum-resistant ovarian cancer, the overall response to any of these therapies is ~10%, with a median progression-free survival of 3–4 months and a median overall survival of 9–12 months. Bevacizumab (Avastin), a humanized, monoclonal antivascular endothelial growth factor antibody, has demonstrated antitumor activity in the platinum-resistant setting and was recently approved by US Food and Drug Administration for combination therapy with weekly paclitaxel, pegylated liposomal doxorubicin, or topotecan. This review summarizes key clinical trials investigating bevacizumab for recurrent, platinum-resistant ovarian cancer and provides an overview of efficacy, safety, and quality of life data relevant in this setting. While bevacizumab is currently the most studied and clinically available antiangiogenic therapy, we summarize recent studies highlighting novel alternatives, including vascular endothelial growth factor-trap, tyrosine kinase inhibitors, and angiopoietin inhibitor trebananib, and discuss their application for the treatment of platinum-resistant ovarian cancer.Keywords: bevacizumab, angiogenesis, ovarian cancer, platinum-resistant ovarian cancer, recurrent ovarian cancer